Against the Individual. Who qualifies as “one”? - Zaharijević, Adriana (Discurso, 2021)
The aim of this paper is to focus specifically on the description of the homo politicus as a sovereign individual who governs itself. Searching to understanding of neoliberalism as a governing rationality through which everything becomes economized.